If a b c = 0 and a x = b , b y = c, c z = a . Then find the value of xyz
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
b = a x c = b y = ( a x ) y a = c z = ( b y ) z = ( ( a x ) y ) z
So we have a = ( ( a x ) y ) z = a x y z .
Take the logarithm of both sides ln a = x y z ln a ln a ln a = x y z x y z = 1
a^x =b
b^y=c
c^z=a
we can substitute a=c^z , c^{xz}=b
and again we can substitute b^y=c
then we get, b^{xyz}=b
If both bases are equal,then the powers also equal.
from that xyz=1 this is final solution.
If a b c = 0 , we have that x y z is any number you like (except 0 ), hence this problem does not have a unique answer. Everything would be alright, though, if the condition a b c = 0 were added (Micah Wood's solution would follow).
a = c^z = b^(yz) = a^(xyz)
a = a^(xyz)
Therefore xyz=1 (Ans.)
Problem Loading...
Note Loading...
Set Loading...
c z = a
a = c z
Since b y = c , then we can substitute in c into our equation, a = c z , so that we get
a = ( b y ) z
And now, since a x = b , we can substitute b into our equation a = ( b y ) z , and get
a = ( ( a x ) y ) z
And through Exponent Rules, we can simplify and end up with
a = a x y z
a 1 = a x y z
1 = x y z